First stage zoeal descriptions of five Galatheoidea species from Western Pacific (Crustacea: Decapoda: Anomura) - Guerao, Guillermo; Macpherson, Enrique; Samadi, Sarah; de Forges, Bertrand Richer; Boisselier, Marie-Catherine (Zootaxa, 2006)
The first zoeal stages of the galatheids Neonida grandis, Agononida squamosa and Munida javieri, and the chirostylids Eumunida annulosa and E. capillata are described and illustrated from laboratory-hatched material obtained from ovigerous females collected from south western Pacific. The morphologies of the first zoeae are compared with the same larval stage of other known anomuran species. The larval characters of Agononida squamosa and Neonida grandis are similar to those described for Agononida incerta. Munida javieri exhibits features not present in other described species of Munida such as the setation of the endopod of the maxillule and the antennal morphology. Eumunida annulosa and E. capillata do not show abbreviated development as in other described chirostylids such as Uroptychus and Gastroptychus, and its larval morphology is equivalent to the first stage of galatheid zoeae. However, many morphological characters of Eumunida species are typically pagurid, such as the two terminal plumose setae of the antennal endopod, the three-segmented endopod of the maxillule, the posterior margin of the carapace without spines, and the scaphognathite with 5 plumose setae and without a posterior lobe.